Obtaining DC and AC isothermal electrical characteristics for RF MOSFET. (April 2015) - Sahoo, A.K.; Fregonese, S.; Scheer, P.; Celi, D.; Juge, A.; Zimmer, T.
Highlights: A methodology to obtain isothermal electrical characteristics of MOSFET. Applied on conventional non-isothermal DC and CW S -parameter characteristics. Characterization on 28 nm bulk CMOS technology at different ambient temperature. Validated of isothermal data through pulsed DC and pulsed RF measurements. Abstract: In this paper we demonstrate a new and simple approach to obtain isothermal electrical characteristics of metal oxide field effect transistor (MOSFET) from conventional non-isothermal measurements. DC and continuous wave (CW) S -parameter measurements are performed at different chuck temperatures ( T chuck ). Knowing the thermal resistance ( R TH ) of the device the variation of DC and AC characteristic due to self-heating can be de-embedded and all the isothermal DC data and AC data above isothermal frequency can be determined. The method is validated by comparing the results with pulsed DC and pulsed RF measurements and found to be in good agreements.